Penyuluhan Pentingnya Pemberian Informasi Tentang Gizi Pada Kehamilan Remaja - Arifa Usman; Ayu Irawati; Susianti Susianti (Pusat Riset dan Inovasi Nasional, 2023)
Amola Village is a village located in Binuang District, Polewali Mandar Regency. Generally, the people there work as farmers, gardeners and civil servants (PNS) as well as entrepreneurs. The method used in this community service activity is a focus group discussion with an interactive question and answer lecture between the servant and pregnant women which lasts for 40 minutes. The number of pregnant women is all pregnant women in Amola village, Binuang sub-district, Polewali Mandar district, with a total of 40 pregnant women. Before the educational activity was carried out, a pre-test was given and after the activity, a post-test was given using a questionnaire instrument containing 10 questions about balanced nutrition in pregnant women. This activity was carried out in Tanete Hamlet, Amola Village, Kec. binuang district. polewali mandarin. Maintaining a nutritional balance in pregnant women is very necessary so that the condition of the mother and fetus remains healthy by providing sufficient food containing carbohydrates and fats as a source of energy. And as a source of protein building blocks, you get a minimum addition of iron, calcium, vitamins, folic acid and energy. The purpose of this community service activity is to increase the knowledge of pregnant women in balanced nutrition. The method is carried out by providing education about balanced nutrition to pregnant women, carried out in Amola Village, Tanete Hamlet, Kec. Binuang Kab. Polewali Mandar. From the results of this community service activity, after being given counseling and given leaflets, pregnant women's knowledge increased after an oral evaluation was carried out.